Qadiyyah Tawassu’ al-‘Alam Bayna Abi Hamid al-Ghazali wa Ibn Rusyd al-Qurtubi - Sujiat Zubaidi Saleh (Universitas Darussalam Gontor, 2009)
This research tries to compare between the position of Abu Hamid alGhazali and the position of Abu al-Walid ibn Rushd in the question of the size of the universe and the possibility of it to be greater or smaller. Al-Ghazali says the possibility of the universe to be greater or smaller than it is, while Ibnu Rushd denies such possibility. According to the latter, if the universe is greater or smaller than it is, it will lead to the possibility of the existence of a magnitude which has no end. In this discussion, Ghazali relies on the Mutakallimin position of the universe concept, while Ibnu Rushd prefers to base his idea of universe on the philosophers such as Aristotle.